Pembangunan Mahasiswa Melalui Program Tarbiah oleh Belia Harmoni di Selangor: Student Development Through Tarbiah Programme by Belia Harmoni in Selangor - Fakhrul Adabi, Fadhilatul Ehsan; Yusof, Muhammed (Jurnal Usuluddin, 2020)
Student development programme is an important programme to produce students with high standard and balance in all aspect. This article will discuss about the implementation of tarbiah (development and training) programme in developing students by Belia Harmoni in Selangor. Belia Harmoni is a platform under a Non-Governmental Organisation (NGO) namely Pertubuhan IKRAM Malaysia (IKRAM) as a specific wing to carry out tarbiah programme for students. This study has used the interview technique to obtain the data. The result of this study found that there are seven tarbiah programme implemented by Belia Harmoni during the student development process; which are usrah (group of discussion circle), katibah (qiamullail), rehlah (picnic), mukhayyam (camping), daurah (lecture on a topic), muktamar (convention) and nadwah (presentation).